2019
DOI: 10.1007/s00238-019-01536-8
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-associated angiosarcoma after autologous breast reconstruction: report of two cases in a plastic surgery unit

Abstract: Radiation-associated breast angiosarcoma is a rare diagnosis but is commonly reported. Angiosarcoma occurring in nonbreast tissue in breasts that have been reconstructed with autologous tissue following mastectomy is extremely rare. In our unit, we have managed two patients with angiosarcoma arising in non-breast tissue autologous reconstructions. Our report emphasises that any tissue treated with radiotherapy-that is, the residual mastectomy skin flaps or non-breast tissue autologous reconstructions-are at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…While the development of secondary angiosarcoma due to radiation is not uncommon in patients who underwent lumpectomy, the development of RAA in reconstructed breast is extremely rare with only four other cases reported in the literature. 4 , 5 , 6 In all four cases, RAA developed after more than 5 years after radiotherapy. In three cases modified radical mastectomy was done.…”
Section: Case Report and Literature Reviewmentioning
confidence: 83%
See 1 more Smart Citation
“…While the development of secondary angiosarcoma due to radiation is not uncommon in patients who underwent lumpectomy, the development of RAA in reconstructed breast is extremely rare with only four other cases reported in the literature. 4 , 5 , 6 In all four cases, RAA developed after more than 5 years after radiotherapy. In three cases modified radical mastectomy was done.…”
Section: Case Report and Literature Reviewmentioning
confidence: 83%
“… 1 After reviewing the literature, we found most of the cases with RAA after breast conserving surgery and only four cases with RAA after mastectomy and autologous breast reconstruction. 4 , 5 , 6 We report a case of RAA after bilateral skin-sparing mastectomy and immediate free flap breast reconstruction to highlight awareness of the disease in an autologous breast reconstruction and the importance of early detection. Furthermore, we want to show that electrochemotherapy, might be applied even in such a rare condition in the palliative intent.…”
Section: Introductionmentioning
confidence: 99%
“…To date, only 3 cases have been reported in the English literature and all 3 occurred in the setting of breast reconstruction followed by radiation therapy for breast cancer. 9,10 The abdominal wall is a popular option as a donor site, and the pedicle TRAM flap and free DIEP flap are several options for breast reconstruction in post mastectomy patients. 11 Hanasono et al 9 reported the first case of angiosarcoma in a 37-year-old patient who had modified radical mastectomy for invasive ductal carcinoma with immediate TRAM flap reconstruction followed by post-operative radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The patient was treated with wide local excision, but developed recurrence requiring extensive removal of the soft tissue of the chest wall. More recently, Yip et al 10 described 2 patients with angiosarcoma in autologous reconstructed breast tissue. The first patient had bilateral mastectomy followed by immediate latissimus dorsi reconstruction and radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation